Could prophylactic antivirals reduce dengue incidence in a high-prevalence endemic area? - Yalda Jafari; Oliver J Brady; Joseph R Biggs; Le Thuy Lien; Huynh Kim Mai; Hien Anh Thi Nguyen; Marnix Van Loock; Guillermo Herrera-Taracena; Joris Menten; Chihiro Iwasaki; Mizuki Takegata; Noriko Kitamura; et al. (Public Library of Science (PLoS), 2024)
Prophylactic drugs against dengue are currently under development. In this study, we explored how such prophylactic approaches might affect dengue cases in four communes of Nha Trang City, Vietnam. A community level dengue transmission survey indicated high levels of previous exposure to dengue (89.7%; 95% CI: 87.2,92.0). We fitted a spatially explicit model to an observed outbreak and simulated likely effectiveness of Case-Area Targeted Interventions (CATI) and One-Time Mass Distribution (OTMD) of drug and vector control strategies. Increasing radius and effectiveness and decreasing delay of CATI was most effective, with drugs being more effective in averting dengue cases than vector control. Using an OTMD approach early in the outbreak required the least number of treatments to avert a case, suggesting that OTMD strategies should be considered as pre-emptive rather than reactive strategies. These findings show that pre-emptive interventions can substantially reduce the burden of dengue outbreaks in endemic settings.